Entry Regulation and Entrepreneurship - Davud Rostam-Afschar (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2012)
I exploit the amendment to the German Trade and Crafts Code in 2004 as a natural experiment to asses the causal effects of this reform on the probabilities of being self-employed and of transition into and out of self-employment using repeated cross sections (2002-2006) of German Microcensus data. I apply the Difference-in-Differences technique in logit models for four occupational groups. The results show that easing the educational entry requirement has fostered self-employment significantly for craftsmen after the reform by increasing the entry probability substantially, while exit rates remained unaffected. Similar, but weaker effects are found for the other occupational groups.
Keywords: L51; J24; M13; 330